Gaussian and Golden Wavelets: A Comparative Study and their Applications in Structural Health Monitoring - Gossler, F. E. [UNESP]; Oliveira, B. R. [UNESP]; Duarte, M. A. Q.; Vieira, J. [UNESP]; Villarreal, F. [UNESP]; Lamblém, R. L. (Sociedade Brasileira de Matemática Aplicada e Computacional - SBMAC, 2021)
In this work, a comparative analysis between Gaussian and Golden wavelets is presented. These wavelets are generated by the derivative of specific base functions. In this case, the order of the derivative also indicates the number of vanishing moments of the wavelet. Although these wavelets have a similar waveform, they have several distinct characteristics in time and frequency domains. These distinctions are explored here in the scale space. In order to compare the results provided by these wavelets for a real signal, they are used in the decomposition of a signal inserted in the context of structural health monitoring.

Neste trabalho, uma análise comparativa entre as wavelets Gaussianas e Golden é apresentada. Tais wavelets são geradas pela derivada de uma função basica específica. Nesse caso, a ordem da derivada também indica o número de momentos nulos da wavelet. Embora essas wavelets tenham formas de onda muito semelhantes, elas possuem várias características distintas nos domínios do tempo e da frequência. Essas distinções são exploradas aqui no espaço de escalas. A fim de comparar os resultados das wavelets para um sinal real, essas wavelets são usadas na decomposição de um sinal inserido no contexto do sistemas de monitoramento de integridade estrutural.
Keywords: gaussian wavelets; golden wavelets; vanishing moments; structural health monitoring; wavelets gaussiana; wavelets golden; momentos nulos; monitoramento de integridade estrutural